The Role of Work Environment and Leadership in Enhancing Employee Performance - Surianto Surianto; Nurfahira Nurfahira (Economics and Digital Business Review, 2024)
This study aims to explore the interaction between the work environment and leadership in influencing employee performance, specifically examining the synergistic effects of a supportive work environment and transformational leadership on innovation, engagement, and productivity. The research employs a qualitative case study approach, focusing on a medium-sized technology company known for its innovative culture and dynamic leadership. Data collection techniques include semi-structured interviews, focus group discussions, and participant observations, providing comprehensive insights into the work environment and leadership practices. The study finds that a supportive work environment, characterized by ergonomic office design, adequate lighting, low noise levels, and a positive organizational culture, significantly enhances the effectiveness of transformational leadership. This synergy boosts employee innovation, engagement, and productivity. Employees operating in such environments report higher job satisfaction and loyalty, indicating the critical role of combining environmental and leadership factors in fostering a productive workplace. The research highlights the importance of investing in a supportive work environment and transformational leadership development to improve organizational performance. Leaders should focus on creating conditions that meet employees' physical and psychological needs while inspiring and motivating them through transformational practices. Future research should address the study's limitations by incorporating quantitative data and exploring diverse organizational contexts to validate and expand upon these findings.